1987
DOI: 10.3109/00016348709103660
|View full text |Cite
|
Sign up to set email alerts
|

Chylothorax as A Complication After Delivery

Abstract: A 23-year old female who developed a chylothorax as a probable complication after delivery is described and a possible mechanism is proposed. Conservative treatment was unsuccessful and the surgical management was complicated by an anatomical variation with the thoracic duct presenting as a plexiform system instead of a single duct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
2

Year Published

1996
1996
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 3 publications
0
13
0
2
Order By: Relevance
“…10,11 With the obstructed expiratory effort of the Valsalva maneuver, high intrathoracic pressure is transmitted to thoracic structures, causing duct rupture after coughing, straining, and/or vomiting. Without malignant or infectious disruption of the duct, it has been postulated that congenital malformation or inherent weakness may be present in these rare individuals.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 With the obstructed expiratory effort of the Valsalva maneuver, high intrathoracic pressure is transmitted to thoracic structures, causing duct rupture after coughing, straining, and/or vomiting. Without malignant or infectious disruption of the duct, it has been postulated that congenital malformation or inherent weakness may be present in these rare individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In the thoracic part of the duct, high stretching forces thus occur on the ductal wall due to high intraluminal and low extraluminal pressure.' [4] In two previous reports, chylothorax was found after prolonged vaginal delivery where extensive external pressure was applied to the abdomen. [4,5] However, in our patient, no external pressure was applied to the abdomen.…”
Section: Discussionmentioning
confidence: 99%
“…Tornling et al [4] reported the first case of chylothorax after delivery and described its mechanism as follows: 'During labor throes, there is initially an increased intrathoracic and intra-abdominal pressure followed by a rapid decrease to negative intrathoracic pressure with persistent high intra-abdominal pressure. In the thoracic part of the duct, high stretching forces thus occur on the ductal wall due to high intraluminal and low extraluminal pressure.'…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations